806 Arterial Oxygen Tension and Outcome After Out-Of-Hospital Cardiac Arrest in Children. (October 2012) - Kanthimathinathan, HK; Scholefield, B; Raman, S; Hussey, A; Haigh, F; Skellet, S; Duncan, H; Peters, M; Morris, K
Abstract : Background: There is good evidence that hyperoxia after resuscitation in the newborn period can be detrimental to neurological outcome and survival. The association between hyperoxia and survival after out-of-hospital cardiac arrest (OHCA) in children has not been evaluated. Methods: A retrospective, observational study of children admitted to 3 PICUs after OHCA (2004–2010). Primary outcome was survival to hospital discharge. Patients were divided into three groups (hypoxia < 8kPa, normoxia 8–40kPa, hyperoxia >40kPa) based on arterial oxygen tension in the first 24 hours. The PaO2 thresholds used are based on recently published literature. Results: 140 patients were identified (51 hypoxia, 60 normoxia, 29 hyperoxia), with the hyperoxia group significantly older than other groups (Table ). The predicted probability of death (PIM2) at PICU admission was similar across the three groups, as was the use of interventions, such as transfer between hospitals and requirement for inotropes. Survival to hospital discharge was only 14% (95% CI: 4–31) in the hyperoxia group against 27% (95% CI: 16–40) in the normoxia group and 37% (95% CI: 24–52) in the hypoxia group (p=0.08). The Odds Ratio for survival in the hyperoxia group was 0.44 (95% CI: 0.13–1.46, p=0.18) compared to the normoxia group. Conclusions: This study has observed a difference in survival related to oxygen tension status, with a trend to worsening survival from hypoxia through to hyperoxia. Confirmation of this preliminary finding is required in a larger cohort before embarking on a randomised controlled trial.